EFEKTIVITAS PERENCANAAN KEBUTUHAN OBAT DENGAN METODE MORBIDITAS TERHADAP KETERSEDIAAN OBAT KEMOTERAPI - Nina Puspitawati; Liza Pristianty; Abdul Rahem; Widawaty Hartono (Jurnal Ilmiah Ibnu Sina (JIIS): Ilmu Farmasi dan Kesehatan, 2021)
One cycle of chemotherapy does not eliminate all cancer cells, therefore it takes a repeated cycle (Williams, et al, 2016), so the guarantee the availability of chemotherapy drugs is needed. An effective drug requirement planning is required to ensure the availability of chemotherapy drug. This study was intended to determine the effectiveness of planning the need for chemotherapy drugs using the morbidity method on the availability of chemotherapy drugs in Dr. Ramelan Navy Hospital. This study was an observational study with a cross sectional study design. The instrument used in this study was the data collection sheet with data sources prescription sheets and sheets of chemotherapy drug reconstitution during 2015-2017. Descriptive data analysis and to determine effective planning methods using indicators of drug availability. The results showed that the planning of drug needs with the morbidity method can better guarantee the availability of chemotherapy drugs and can minimize drug shortages compared to the consumption method that has been done so far in Dr. Ramelan Navy Hosptal. So it can be concluded that in this study, the morbidity method is effective in meeting the needs of chemotherapy drugs.